IMPLEMENTATION OF THE AHP-TOPSIS METHOD IN DECISION MAKING OF SOCIAL ASSISTANCE RECIPIENTS IN KARANGANYAR GUNUNG SEMARANG - Dinda Locita Fitri; Aji Supriyanto (Jurnal Teknik Informatika (Jutif), 2022)
The government's program of Social Assistance (Bansos) aims to improve the welfare of poverty in order to increase economic value, targeting that the recipients of the social assistance are the poor. There are still some obstacles in receiving social assistance, which are considered to be uneven, duplicate data and mistargeted. There are various models of determining poverty, one of which is based on calculations from the Central Statistics Agency (BPS). These provisions are used by the government in providing social assistance to be right on target. The determination of social assistance recipients according to BPS has 14 poverty criteria, namely: eating as much as a day, medical expenses, sources of income, sources of lighting, cooking fuel, toilet facilities, consumption of types of food, floor area, types of walls, sources of drinking water, savings , type of floor, buying clothes, and education of the head of the household. Using the Analytical Hierarchy Process (AHP) and the Technique Order Preference by Similarity to Ideal Solution (TOPSIS) which are used to rank Social Assistance recipients. The AHP method is used to weight the poverty criteria, while the TOPSIS method is used to rank alternative social assistance recipients, so as to produce recommendations for social assistance recipients. The test was carried out using 45 data from prospective social assistance recipients, the result was that the eligible recipients were in first place A4 with a value of -11.09028, in second place A5 with a preference value of -9.40301, third place A2 with a value of -7.30247 , fourth in A1 with a preference value of -4.33412, and fifth in A3 with a preference value of 9.35849.